2020
DOI: 10.3389/fendo.2020.556962
|View full text |Cite
|
Sign up to set email alerts
|

From Influenza Virus to Novel Corona Virus (SARS-CoV-2)–The Contribution of Obesity

Abstract: From the beginning of 2020, the governments and the health systems around the world are tackling infections and fatalities caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) resulting in the coronavirus disease 2019 (COVID-19). This virus pandemic has turned more complicated as individuals with co-morbidities like diabetes, cardiovascular conditions and obesity are at a high risk of acquiring infection and suffering from a more severe course of disease. Prolonged viral infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 120 publications
0
29
0
Order By: Relevance
“…Pique-Regi et al 41 reported low expression of these receptors in placentae from SARS-CoV-2-positive women, suggesting a low likelihood of vertical transmission, although they suggested that SARS-CoV-2 may interact with other proteins to use alternative routes to invade cells. It may also be possible that comorbidities, such as chronic hypertension and those related to chronic inflammation, such as obesity and diabetes, can affect the renin-angiotensin-aldosterone system and facilitate the vertical transmission of SARS-CoV-2 [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Pique-Regi et al 41 reported low expression of these receptors in placentae from SARS-CoV-2-positive women, suggesting a low likelihood of vertical transmission, although they suggested that SARS-CoV-2 may interact with other proteins to use alternative routes to invade cells. It may also be possible that comorbidities, such as chronic hypertension and those related to chronic inflammation, such as obesity and diabetes, can affect the renin-angiotensin-aldosterone system and facilitate the vertical transmission of SARS-CoV-2 [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Higher BMI has been associated with influenza (Maier et al., 2018). Obese patients frequently experience worse outcomes related to infectious diseases than their nonobese counterparts (Bhattacharya et al., 2020). Our study identified elevated incidence rate for 9‐AURTIs but not for total RTIs, common cold, and influenza among males.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that COVID-19 patients with diabetes have higher lymphopenia incidence and increased proinflammatory biomarkers than those without diabetes (67,68). Moreover, increased inflammation such as elevated IL-6 and TNF levels were also observed in obese patients, thus favors COVID-19 disease progression, and worsens the lung and heart functions (69). Therefore, obesity is also an important predisposing factor for this phenomenon.…”
Section: Inflammationmentioning
confidence: 99%